THE INFLUENCE OF DIGITAL HEALTH COMPETENCE ON HEALTHCARE SERVICE PERFORMANCE AT KING ABDULLAH MEDICAL CITY, 2026: A QUANTITATIVE APPROACH USING STRUCTURAL EQUATION MODELING (SEM-PLS) - Ali Mohammed Albeah; Hafizah Che Hasan (PT. Jurnal Center Indonesia Publisher, 2026)
Digital transformation has fundamentally reshaped healthcare service delivery worldwide, particularly in tertiary hospitals that rely heavily on integrated digital systems such as Electronic Health Records (EHRs), telemedicine, clinical decision support systems, and data-driven healthcare technologies. Despite rapid technological advancement, limited empirical evidence explains how healthcare professionals’ digital competence contributes to healthcare service performance within the context of healthcare transformation in Saudi Arabia. Previous studies have primarily focused on technological adoption or technical outcomes, while the psychological and organizational mechanisms underlying digital healthcare performance remain underexplored. Drawing upon the Job Demands–Resources (JD-R) Theory and Resource-Based View (RBV), this study investigates the influence of Digital Health Competence (DHC) on Healthcare Service Performance (HSP), examining the mediating role of Work Engagement (WE) and the moderating role of Organizational Support (OS). This study employed a quantitative cross-sectional explanatory design using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected from 312 healthcare professionals at King Abdullah Medical City (KAMC), Saudi Arabia, selected through stratified random sampling. The study included physicians, nurses, pharmacists, and allied healthcare professionals actively utilizing digital healthcare systems in clinical practice. Measurement instruments were adapted from internationally validated scales, including the European Digital Competence Framework for Health Professionals, Utrecht Work Engagement Scale (UWES), and Perceived Organizational Support Scale. Data analysis included assessment of the measurement model, structural model evaluation, mediation analysis, moderation analysis, effect size (f²), predictive relevance (Q²), and model fit indices. The findings demonstrated that Digital Health Competence had a positive and significant effect on Healthcare Service Performance (β = 0.328, p < 0.001) and Work Engagement (β = 0.541, p < 0.001). Work Engagement significantly influenced Healthcare Service Performance (β = 0.462, p < 0.001) and partially mediated the relationship between Digital Health Competence and Healthcare Service Performance (β = 0.250, p < 0.001). In addition, Organizational Support significantly moderated the relationship between Digital Health Competence and Work Engagement (β = 0.217, p < 0.001). The structural model demonstrated substantial explanatory power (R² HSP = 0.683) and satisfactory predictive relevance. This study contributes theoretically by extending the application of JD-R Theory and RBV within the context of digital healthcare transformation in tertiary hospitals. The study proposes an integrated model demonstrating that digital competence functions not only as a technical capability but also as a strategic personal resource that enhances work engagement and healthcare service quality. Practically, the findings emphasize the importance of strengthening digital competency development, supportive organizational climates, and adaptive digital infrastructures to improve healthcare professionals’ performance and accelerate sustainable healthcare transformation in Saudi Arabia.